Enseñar y aprender español en un grupo grande de enseñanza secundaria en Gabón - Eugénie EYEANG (Ediciones Universidad de Salamanca, 2009)
RESUMEN: En el artículo se proponen respuestas contextualizadas para la enseñanza del español en la educación secundaria de Gabón, y en particular en los grupos grandes de los Institutos de Libreville. El trabajo es consecuencia del avance logrado en la tesis doctoral de la autora sobre la enseñanza del español en Gabón. ABSTRACT: In this paper the author proposes contextualised answers for Spanish language teaching in Gabonese secondary schools, and especially in the large groups of Libreville city. This article is a consequence of the doctoral theses about Spanish language teaching in Gabon, written and defended in Grenoble University by Eugenie Eyeang.